2013
DOI: 10.1177/0309324713489297
|View full text |Cite
|
Sign up to set email alerts
|

New approaches to optimize strain behavior of Al6082 during equal channel angular pressing

Abstract: Equal channel angular pressing is one of the attractive methods of severe plastic deformation techniques to fabricate ultrafine grained materials. In this study, eight different equal channel angular pressing configurations including the punch shape, sample preform and die geometry have been analyzed using finite element method to achieve materials with the high effective strain magnitude, better strain distribution uniformity and less required pressing force. The results show that the combination of punch sha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 30 publications
(37 reference statements)
0
9
0
Order By: Relevance
“…Hollomon's relationship was utilized to characterize the material behavior, in accordance with Eq. (4) in which σ, K, ε and n are effective von-Mises stress, strength coefficient, effective plastic strain and strain hardening exponent, respectively [20]. The values of strength coefficient (K) and strain hardening exponent (n) were obtained via the true stress -strain curve for the as-received billet.…”
Section: Numerical Proceduresmentioning
confidence: 99%
“…Hollomon's relationship was utilized to characterize the material behavior, in accordance with Eq. (4) in which σ, K, ε and n are effective von-Mises stress, strength coefficient, effective plastic strain and strain hardening exponent, respectively [20]. The values of strength coefficient (K) and strain hardening exponent (n) were obtained via the true stress -strain curve for the as-received billet.…”
Section: Numerical Proceduresmentioning
confidence: 99%
“…It has been reported that external conditions, such as die geometries, processing, and friction, as well as internal conditions, such as work hardening and the strain rate sensitivity of the material, may contribute to inhomogeneity of the processed material [16][17][18][19][20][21]. For example, Ebrahimi et al [21] studied the influence of punch and die geometry on strain distribution of the aluminum alloy processed by ECAP. Inhomogeneity in structure can be assessed by a factor known as the inhomogeneous factor (IF) or coefficient of standard deviation and can be expressed by the following equation [21]:…”
Section: Introductionmentioning
confidence: 99%
“…For example, Ebrahimi et al [21] studied the influence of punch and die geometry on strain distribution of the aluminum alloy processed by ECAP. Inhomogeneity in structure can be assessed by a factor known as the inhomogeneous factor (IF) or coefficient of standard deviation and can be expressed by the following equation [21]:…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Many scholars have developed varied SPD processes for components with different shapes. 14 Constrained groove pressing (CGP), 15 equal-channel angular pressing (ECAP), 16,17 tube channel pressing (TCP) 18 and repetitive tube expansion and shrinking (RTES) 19 are some of them.…”
Section: Introductionmentioning
confidence: 99%